Integrasi Hasil MRP dengan Kedatangan Supplier untuk Part Category A Menggunakan Metode RCCP dan Simulasi - Yuni Erfianti; Arief B. Suharko (Syntax Idea)
Supply Chain Management (SCM) is a series of activities to process raw goods until they are ready for use by consumers, which includes the flow of goods. The flow of goods occurs as a result of the need for material purchases and the production process to meet consumer demand. After the material requirements are calculated and determined by the company, the company needs to find and order suppliers to send the goods to the warehouse. In reality, the process is not always smooth, companies have difficulty estimating the number of goods needed for efficient and maximum production each month. There is always stock in the warehouse, even more than the capacity of the warehouse itself. Therefore, this research focuses on integrating the results of MRP (Material requirements planning) with supplier arrivals which focuses on category A parts or components which are determined based on warehouse space usage and the value of the part or component item itself. This part is then calculated using the RCCP method and its effectiveness is verified using discrete event simulation in the Jaamsim program. The results of research at PT XYZ show that there are 4 category A part or component items that have a significant effect. The four items are Cover L Side, Radiator Assy, Case Comp Mission and Pulley Assy Driven. After calculating the RCCP for these four part items, it was found that the arrival period of the supplier needed to be determined to ensure the availability of goods at the right time and in the right quantity. This result is supported by the Jammsim simulation which shows that the queue for goods becomes shorter and stock fluctuations become lower. In addition, with more careful arrival planning there is the potential to reduce the frequency of delivery trips from suppliers where supplier trucks can potentially make more than 1 trip per delivery, there by saving on truck rental or investment costs.